Investigate the needs of students and educators in the development of a learning model for reading comprehension in middle school - Wulandari, Ayu; Sayuti, Suminto A.; Wiyatmi, Wiyatmi (Edelweiss Applied Science and Technology, 2025)
This research aims to describe a framework for investigating the needs of students and educators in developing reading comprehension learning models in junior high schools. The research was carried out at Magelang City Middle School because Magelang City is one of the oldest cities in Indonesia, whose existence is very strategic in the center of Central Java. Several elements in its vision are smart people and smart living, which means education and the development of technology-literate human resources, research support, the development of the socio-cultural character of the community, as well as easy access to educational services. This research was conducted from August to September 2023. The subjects in this research were 85 students and 3 educators from 3 schools selected using the purposive sampling method. Data collection techniques included questionnaires and interviews. Data analysis techniques employed qualitative descriptive analysis. The results of the research show that investigations to analyze the needs of students and educators in developing reading comprehension learning models in junior high schools are needed to improve students’ reading comprehension skills. In the implementation of learning to read, comprehension is not yet optimal because an innovative model that supports 21st-century competence has not been fully designed. The learning model is applied to language skills in addition to reading skills. The use of technology has not been fully utilized, and texts containing local wisdom have not been utilized. The use of teaching materials is limited to government-issued textbooks. Students still need a good understanding to find text ideas, connect text ideas, and conclude the text.